2005
DOI: 10.1093/cercor/bhj075
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of the Spontaneous Phase Transition during Bimanual Coordination

Abstract: Repetitive bimanual finger-tapping movements tend toward mirror symmetry: There is a spontaneous transition from less stable asymmetrical movement patterns to more stable symmetrical ones under frequency stress but not vice versa. During this phase transition, the interaction between the signals controlling each hand (cross talk) is expected to be prominent. To depict the regions of the brain in which cortical cross talk occurs during bimanual coordination, we conducted event-related functional magnetic resona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
81
2
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(94 citation statements)
references
References 78 publications
9
81
2
2
Order By: Relevance
“…As such, we have partial data (13 subjects) for right-handed tapping. However, nondominant left-hand movements have been reported to fluctuate more in the BP mode than those of the dominant right hand (Semjen et al, 1995;Aramaki et al, 2006). Thus, we calculated performance indices using left-hand tapping data for all 18 subjects and used it in the correlation analysis with brain activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, we have partial data (13 subjects) for right-handed tapping. However, nondominant left-hand movements have been reported to fluctuate more in the BP mode than those of the dominant right hand (Semjen et al, 1995;Aramaki et al, 2006). Thus, we calculated performance indices using left-hand tapping data for all 18 subjects and used it in the correlation analysis with brain activity.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between the stability of periodic bimanual movement and brain activity has previously been studied by comparing epoch-related brain activity during in-phase and antiphase movements (Sadato et al, 1997;MeyerLindenberg et al, 2002;Aramaki et al, 2006Aramaki et al, , 2010Kraft et al, 2007;Müller et al, 2009). However, relatively few studies have focused on transient brain activity during the movement initiation or pattern-switching phases (Aramaki et al, 2006(Aramaki et al, , 2010Kraft et al, 2007;De Luca et al, 2010). Our findings are consistent with previous studies reporting greater transient brain activity in the putamen during antiphase movements relative to in-phase movements (Kraft et al, 2007;Aramaki et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using event-related functional MRI (fMRI), Aramaki et al (2006a) depicted the transition-related activity in multiple right-lateralized parieto-premotor regions.…”
Section: Introductionmentioning
confidence: 99%
“…Aramaki et al (2006a) concluded that at the phase transition, the cortical neural cross-talk occurs in distributed networks upstream of the primary motor cortex through asymmetric interhemispheric interaction.…”
Section: Introductionmentioning
confidence: 99%